A strategy to optimize soil phosphorus reserve: A study based on native maize of Mexico and genotype selection - Salazar-Mejía, Selene Guadalupe (2024)
Continual removal of phosphorus (P) by the crop gradually decreases soil fertility and drives the need for fertilizer inputs for agricultural production. Phytate is considered as the major storage pool for P in the seeds, but its contribution to human nutrition is low. The objective of this study was to characterize quantitative P concentrations (phytate, inorganic P and total P) of 50 native maize genotypes of Zea mays L. of the Patzcuaro lake, Michoacan, Mexico. The average total P and phytate concentration observed across all the genotypes was 3,1, 2,64, and 0,43 mg g-1, respectively. The relationship between phytate and total P was strong (r= 0,98**). This clearly suggests that with an increase in total P there is a corresponding increase in phytate concentration. Cluster analysis of data indicated five distinct groups with 1, 14, 11, 15 and 9 genotypes, respectively. Clusters I and II contained low phytate genotypes (1,74 mg g-1) while cluster V grouped most of the high phytate (4,9 mg g-1) contenting genotypes. Principal component analysis and F test showed the attributes more influencing group separation. Those attributes were total P and phytate. The first two components explained the 95% of the accumulation variation among groups. The race of the genotypes, however, was no clearly related to the group differentiation. These observations provide the first study on the genetic variety for breeding maize with lower P concentration to reduce P extraction from maize field at harvest.